2013
DOI: 10.1111/jgh.12402
|View full text |Cite
|
Sign up to set email alerts
|

Impact of IL28B polymorphisms on 24‐week telaprevir‐based combination therapy for Asian chronic hepatitis C patients with hepatitis C virus genotype 1b

Abstract: The IL28B single nucleotide polymorphism still remained informative as a predictor of SVR to 24-week telaprevir-based triple combination therapy for East Asian patients infected with hepatitis C virus genotype 1b.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 27 publications
(124 reference statements)
3
25
0
1
Order By: Relevance
“…107,108 The SVR rates increased to 70%-82% with an additional 12 weeks of PEG-IFN α plus RBV, except for one small trial 112 enrolling the most difficult-to-treat partial responders and nonresponders, which showed an SVR rate of 27%. 107,[109][110][111][112][113][114][115] In line with Western reports, IL-28B genotypes and RVR strongly affected the SVR rates in Asian HCV-1 patients receiving BOC-or TVR-based triple therapy. 107,109,115 Because the numbers of Asian HCV-1 patients who received BOC were low, and no studies were designed for TVR-based RGT in Asian HCV-1 patients, the optimized strategies for shortening treatment duration on the basis of early viral kinetics and IL-28B genotypes have not yet been determined.…”
Section: Boc or Tvr-based Triple Therapy In Asian Patients With Chronsupporting
confidence: 68%
“…107,108 The SVR rates increased to 70%-82% with an additional 12 weeks of PEG-IFN α plus RBV, except for one small trial 112 enrolling the most difficult-to-treat partial responders and nonresponders, which showed an SVR rate of 27%. 107,[109][110][111][112][113][114][115] In line with Western reports, IL-28B genotypes and RVR strongly affected the SVR rates in Asian HCV-1 patients receiving BOC-or TVR-based triple therapy. 107,109,115 Because the numbers of Asian HCV-1 patients who received BOC were low, and no studies were designed for TVR-based RGT in Asian HCV-1 patients, the optimized strategies for shortening treatment duration on the basis of early viral kinetics and IL-28B genotypes have not yet been determined.…”
Section: Boc or Tvr-based Triple Therapy In Asian Patients With Chronsupporting
confidence: 68%
“…Predictors of treatment outcome by telaprevir‐based triple therapy have been reported in real‐world clinical practice in Japan . These reports found that prior treatment response to PEG‐IFN α /ribavirin, IL‐28B genotype and liver fibrosis had an effect on the success of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of telaprevir to the PEG IFN‐α/RBV combination remarkably improves the SVR rate in both treatment‐naïve and previously treated patients, which may decrease the value of IL28B SNP as a predictor of SVR . However, in the 24‐week telaprevir‐based triple therapy for HCV G1b Japanese patients, IL28B SNP still remained informative as a strong predictor of SVR: the rate of 94–97% for those with the rs8099917 major genotype TT and 50–56% for those with the minor genotype TG/GG . Therefore, this study focused on patients with the unfavorable IL28B minor genotype and analyzed factors associated with SVR in such a refractory patient subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, single nucleotide polymorphisms (SNP) near the interleukin‐28B ( IL28B ) gene was one of the most important predictors of SVR in PEG IFN‐α/RBV dual combination therapy . Although it was reported that the value of the IL28B SNP is attenuated with 48‐week PEG IFN‐α/RBV/telaprevir triple therapy in a predominantly Caucasian cohort, the SNP remained informative as a predictor of SVR to 24‐week PEG IFN‐α/RBV/telaprevir triple therapy for East Asian genotype 1b (G1b) patients . In a previous East Asian cohort treated with the 24‐week telaprevir‐based triple therapy, the SVR rate was very high (94–97%) in patients with the rs8099917 genotype TT ( IL28B major genotype), whereas it was relatively low (50–56%) in those with the genotype TG/GG ( IL28B minor genotype) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation